The genus Arthropterygius Maxwell (Ichthyosauria: Ophthalmosauridae) in the Late Jurassic of the Neuquén Basin, Argentina - Fernández, Marta Susana (2012)
Recent discovery of a skull and forefin of an ophthalmosaurid ichthyosaur from the Tithonian (Late Jurassic) of the Neuquén Basin, Argentina, shows a peculiar morphology of the braincase and forefin, including the opening for internal carotids situated on the posterior surface of the parabasisphenoid and dorsoventral compression of the posterior part of the humerus. These characteristics appear unique within ophthalmosaurids, and probably within Ichthyosauria, and are diagnostic of the genus Arthropterygius, a taxon to date only known from the Oxfordian-Kimmeridgian of Northwest Territories, Canada. The new finding increases the knowledge of this peculiar ophthalmosaurid and represents, up to the present, the first evidence for a potentially widespread and climatically diverse distribution of this rare genus.